Monocyte Distribution Width, a Novel Biomarker for Early Sepsis Screening and Comparison with Procalcitonin and C-Reactive Protein - Meraj, Fatima; Shaikh, Sumera; Maqsood, Sidra; Kanani, Fatima; Khan, Hamza; Jamal, Saba (Journal of Laboratory Physicians, 2023)
Objectives Monocyte distribution width (MDW) can be used for the early recognition of sepsis. The study compared the diagnostic accuracy of the MDW with two well-known sepsis biomarkers, procalcitonin (PCT) and C-reactive protein (CRP).Materials and Methods A study was conducted from July 2021 to October 2021, on 111 patients admitted to the Indus Hospital and Health Network. Patients from the ages of 1 to 90 years were enrolled if hospitalized for more than 24 hours for suspected sepsis to avoid inclusion of patients who had short-term stay in the emergency department. According to the Sequential Organ Failure Assessment score, the clinical team did the characterization of cases as with sepsis or without sepsis. SPSS version 24 was used, and the diagnostic accuracy of MDW was assessed and compared using the area under the curves (AUCs) acquired from receiver operating characteristic curves. Pearson's chi-square/Fisher's exact test (as per need) was applied to determine the association. A p-value of less than 0.05 was considered significant.Results Among 111 patients, 81 (73%) patients were labeled with sepsis and 30 (27%) were without sepsis. We have reported significantly higher MDW, PCT, and CRP levels in septic patients (p < 0.001). The AUC of MDW was comparable with PCT (0.794). Significant cutoff value for the MDW was greater than 20.24 U with 86% sensitivity and 73% specificity.Conclusion MDW may have a predictive ability similar to PCT and CRP in terms of sepsis and, thus, can be used as a standard parameter for the timely diagnosis of sepsis.
Keywords: biomarkers; procalcitonin; C-reactive protein; monocyte distribution width; sepsis